The Screening of Antioxidant Activities of Meniran Plants (Phyllanthus niruri Linn) and Guava Leaves (Psidium guajava Linn) Combination Using DPPH Free Radical Method - Wimpy Wimpy; Tri Harningsih; Yesti Nanda Sisvitara (Biomedika, 2020)
Degenerative disease is a serious health problem and causes a lot of deaths in Indonesia. One of the most dangerous degenerative diseases is cancer. Free radicals play a role in oxidative stress in the later stages of carcinogenesis. Antioxidant delays or inhibits cellular damage mainly through its free radical scavenging property. Meniran plants and guava leaves have high radical-scavenging activities. The previous studies reported that the combination of ginger and Meniran plant extract has a stronger antioxidant activity than the extract of a single plant. This research aims at determining the antioxidant activities of Meniran plants and guava leaves compared with its singular form. This research was conducted from October to December 2016 at the Chemical Laboratory of Nasional Health Science Institute and the Center for Development and Research of Medicinal Plants and Traditional Medicine, Tawangmangu, Karanganyar. The antioxidant activity assay was done using DPPH free radical method and vitamin C was used as the control. They were measured with UV-Vis Spectrophotometer. This study concludes that the IC50 value of Meniran plants was 30.689 ppm and the IC50 value of guava leaves was 13.7859. The IC50 values of Meniran plant and guava leaf combination with various ratios were 20.6095 ppm (1:1), 12.5629 ppm (1:2), and 16.841 ppm (2:1). The combination of Meniran plant and guava leaf extract (1: 2) had the strongest antioxidant activity of 12.56 ppm.